Synergistic effects of a carbohydrate-controlled diet and Cuminum cyminum herbal infusion on metabolic syndrome - Maria Aslam; Habib-ur-Rehman; Tabussam Tufail; Yousaf Almehmadi; Wajd Abdullatif Abualamah; Abdullah R. Alzahrani; Imran Shahid (Frontiers in Nutrition, 2025)
BackgroundMetabolic syndrome (MetS) is a growing global health concern and a major risk factor for conditions such as diabetic nephropathy and atherosclerosis. It is marked by chronic inflammation, insulin resistance, and dyslipidemia. Dietary interventions, including carbohydrate-controlled diets, have shown potential in improving metabolic outcomes. Cuminum cyminum (cumin), containing the bioactive compound cuminaldehyde, is known for its hypoglycemic and antioxidant properties.AimThis study aimed to evaluate the combined effect of a carbohydrate-controlled diet and cumin herbal infusion on metabolic and biochemical parameters in patients with metabolic syndrome.MethodsA pre- and post-interventional study was conducted on 132 patients (aged 18–60 years) diagnosed with MetS based on the ATP III criteria. Participants were recruited from the University of Lahore Teaching Hospital (ULTH) through purposive sampling and were randomly assigned to control and intervention groups (n = 66 each). The intervention group (INEG) received a carbohydrate-controlled diet and cumin herbal infusion for 8 weeks. Anthropometric, biochemical, and physiological parameters were assessed at baseline and post-intervention. A two-way repeated measures ANOVA was used for statistical analysis.ResultsSignificant improvements were observed in body mass index (BMI), body weight, and lipid profile parameters (p < 0.005). The intervention group showed notable reductions in triglycerides, low-density lipoprotein (LDL), and fasting blood glucose levels compared to the control group (CG).ConclusionA carbohydrate-controlled diet combined with cumin herbal infusion may support glycemic control and improve lipid metabolism in individuals with metabolic syndrome. This combined approach shows potential as an adjunct dietary strategy for managing cardiometabolic risk factors.